P02-69 - Social and clinical characteristics convicted mentally ill males and females, which are needed inpatient treatment - Malkin, D. (European psychiatry, 2010)
In aim to give a more precise definition dynamic treats of mental disorders in convicted population, criteria of their penitentiary legal capacity 160 subjects were examined. Participants were 73,2% males, and 26,8% females. The revealed unique features of the inmates reflect general tendency of increasing the number of marginal persons in the institutions of confinement. They were: low parental family status, drug abuse heredity loading, insufficient education level, limited professional skills, releasing from statuary service commitment, negative interpersonal and employment history. Specific features of female mentally ill inmates were the following: commitment due to offenders against persons, adolescence and early adulthood age, correspondingly commitment and psychiatric treatment at first time, the country side residence, psychiatric heredity loading, and repeated auto aggressive acts. They demonstrated desadaptation in the institutions of confinement, aggressiveness to others inmates and the stаff members, scratching and attempts of suffocation. The last one was the reason for hospitalization. Moreover, they were needed in long term treatment. Prevalence of personality and non psychotic disorders were registered. Different features were specific for the male sample. Among them - institution of criminal proceedings against property, history of long-term commitment, recidivism and reiterated involvement in criminal proceedings and correctional units, city residence, low status in criminal subculture, scratching and declaration go on hunger strike, practice blackmail and opposite behavior against administration of state penitentiary. They have often resorted to psychiatrists, and were needed in repeated hospitalizations. Brain damages, prevalence of internal symptoms in psychogenic disorders and psychotic states.